Integrating ecological and genetic structure to define management units for caribou in Eastern Canada - Bernatchez, Louis; St-Laurent, Martin-Hugues; Yannic, Glenn; Ortego, Joaquin; Côté, Steeve D.; Taillon, Joëlle; Beauchemin, Alexandre; Dussault, Christian (Conservation Genetics, 2016)
Genetic diversity is a key parameter to delineate management units, but many organisms also display ecological characteristics that may reflect potential local adaptations. Here, we used ecological and genetic information to delineate management units for a complex system involving several ecotypes of caribou (Rangifer tarandus) from Québec and Labrador, eastern Canada. We genotyped 560 caribou at 16 microsatellite loci and used three Bayesian clustering methods to spatially delineate and characterize genetic structure across the landscape. The different approaches employed did not converge on the same solution, and differed in the number of inferred genetic clusters that best fit the dataset but also in the spatial distribution of genetic variation. We reconciled variability among the methods using a synthetic approach that considers the sum of the partitions obtained by each of them and retrieved six genetically distinct groups that differ in their spatial extent across the range of caribou in the study area. These genetic groups are not consistent with the presently defined ecological designations for this species. Combining both genetic and ecological criteria, we distinguished eight independent management units. Overall, the management units we propose should be the focus of conservation and management actions aimed to maximize genetic and ecological diversity and ensure the persistence of caribou populations inhabiting increasingly disturbed landscapes.